Slovenski podjetniški observatorij 2003 - Rebernik, Miroslav; Močnik, Dijana; Knez Riedl, Jožica; Tominc, Polona; Širec, Karin; Rus, Matej; Krošlin, Tadej; Dajčman, Silvo (2004)
Slovenian Entrepreneurship Observatory 2003. Understanding what is happening in Slovenian enterprises is important not only in order to pursue an appropriate economic policy but also in order to find the advantages and disadvantages of Slovenian companies in comparison with enterprises in other European countries. The goal of making Europe the most dynamic economy in the world by 2010 will be difficult to achieve. If Slovenia wishes to join the most developed European countries, it will have to speed up its economic growth. Without successful and high-growth enterprises and without the dynamic process of establishing new enterprises, it will not be possible to reach this target. Slovenian Entrepreneurship Observatory 2003 consists of several research issues. In the first part, a short review of the current level of entrepreneurship is given, outlined on the basis of economic and statistical data. In the second part, a number of topics, based on a survey of a sample of 672 enterprises are dealt with. We studied the relationship between banks and small and medium-sized enterprises, female entrepreneurship, clustering, social responsibility of companies and the development of competences.
Keywords: podjetniška demografija; Slovenski podjetniški observatorij; bančno financiranje MSP; žensko podjetništvo; okoljska odgovornost; Companies Demography; Slovenian Entrepreneurship Observatory; Bank Financing of SMEs; Female Entrepreneurship; Social Responsibility